Simulation and evaluation of the peak temperature in LED light bulb heatsink. (June 2016) - Sun, Lixia; Zhu, Jianxin; Wong, H.
Abstract: Heat dissipation in LED light bulb has been one of the key factors in affecting the efficiency and lifetime of the LED. The commercially available high-power LED light bulbs often come with a bulky heatsink to keep the temperature of the light bulb in a reasonable range. Unfortunately, the heatsink designs of most of the commercial products are not optimized in terms of cooling efficiency, dimension, and material cost. Indeed, optimization of the heatsink design is a time-consuming and sophisticated process. It requires a powerful computational fluid dynamics tool to perform computer simulation. With the aid of computer simulation based on a simple heat conduction model together with some measurement results, this work presents a rapid evaluating tool for predicting the peak temperature of a heatsink by using the concept of effective heat conductivity. It provides a simple way to predict the peak temperature change for different designs. Highlights: A rapid tool for estimating the peak temperature of LED heatsink based on effective conductivity approximation. A simple way to predict the peak temperature change after varying the heatsink design.